Investigation of the construction of probabilistic low cycle fatigue design curves at strain cycling - Bazaras, Žilvinas (Transport, 2005)
Probabilistic methods are based on the use of statistical data about mechanical characteristics and lifetime at cyclic loading of a material. In this investigation statistical low cycle fatigue tests were carried out and mechanical characteristics of three materials (steel of grades 15X2MFA and 45 and aluminium alloy D16T1), representing all possible variations of cyclic properties (fatigue, quasi ‐ static and intermediate mode of fracture) were determined experimentally. Based on the obtained data the analysis of design curves of equal fracture probability for steels 15X2MFA and 45 and aluminium alloy D16T1 at strain low cycle loading was performed and the design curves were compared with the experimental ones. First Published Online: 27 Oct 2010